Odpowiedzi

2010-02-25T16:18:11+01:00
{2x+3y=14 |*2
{3x-2y=8 |*3

{4x + 6y = 28
{9x - 6y = 24
____________
13x = 52 |:13
x = 4
3*4 - 2y=8
12-2y=8
-2y = -4 |:(-2)
y= 2
{x=4
{y=2

Drugi
{0,5x-2y=8 |*(-4)
{2x+5y=6
{-2x + 8y = -32
{2x + 5y = 6
_____________
13y = -26 |:13
y = -2
2x + 5*(-2) = 6
2x - 10 = 6
2x = 16 |:2
{x = 8
{y = -2
2010-02-25T16:31:29+01:00
2x+3y=14
3x-2y=8

2x=14-3y/:2
3x-2y=8

x=7-1,5y
3*(7-1,5)-2y=8

x=7-1,5y
21-4,5y-2y=8

x=7-1,5y
-6,5y=8-21/:(-6,5)

x=7-1,5y
y=2

x=7-1,5*2
y=2

x=4
y=2